Entertainment ≠ Culture: Reclaiming Epistemic Precision as Decolonial Practice - Arnold Udoka (Universitas Negeri Makassar, 2026)
This paper identifies a foundational epistemic violence in Nigerian public, policy, academic, and non-state discourse: the interchangeable use of “entertainment” and “culture.” Grounded in decolonial epistemology (Smith, 2012; Mignolo, 2007), the study argues that this substitution is not semantic slippage but the systematic dismantling of indigenous knowledge categories. Through critical discourse analysis of 120 texts published between 2020 and 2025, and a controlled transmission experiment with 40 participants, we demonstrate that entertainment is a minuscule aspect of culture, not its synonym. When “entertainment” substitutes for “culture,” 82.5% to 86.2% of epistemic components disappear from discourse, and 74.4% to 87.2% of cultural knowledge is deleted in transmission. Analysis reveals four epistemic boundaries (purpose, time, authority, and scope) that operate on distinct logics. Entertainment runs on audience amusement, clock time, and producer authority, transmitting only 10 to 15 percent visible form. Culture runs on community continuity, body time, and elder/knowledge-keeper authority, transmitting 85 to 90 percent invisible function, including cosmology and rules of transmission. Collapsing these categories constitutes epistemic violence by erasing the conditions that make indigenous knowledge transmissible (Spivak, 1988; Smith, 2012). We propose the CARE Protocol as a decolonial standard: Context First, Authority Present, Rules of Transmission, and Exit Ritual. The study connects this protocol to choreographic jurisprudence (Udoka, 2026, para. 4), positioning lexical justice as the first statute in a decolonial legal code. Recommendations include legal separation of “culture” and “entertainment” in national policy, renaming university departments to “Cultural Transmission Studies,” media style-guide reform, and grant-compliance mandates that require CARE. The study concludes that lexical justice is the necessary first step toward epistemic justice and decoloniality.